The gene expression of class III inhibitors of apoptosis in arteriosclerotic disease - Gil-Kulik, Paulina; Bogucka-Kocka, Anna; Zubilewicz, Tomasz; Wojcieszek, Agnieszka; Filas, Małgorzata; Dudek, Ilona; Chomik, Piotr; Kotuła, Lidia; Karwat, Jolanta; Feldo, Marcin; Niedojadło, Alicja; Kocki, Janusz (Polish Journal of Public Health, 2014)
Introduction. Recent research shows that programmed cell death has great importance in the pathomechanism of atherosclerosis. The BIRC5 and BIRC6 genes belong to Class III IAPs with the anti-apoptotic effect. The proteins display multidirectional action. According to the available literature, in addition to the effect of apoptosis inhibition they also display other properties. It is suggested that they play an important role in the processes of proliferation and cellular differentiation.Aim. The aim of the study was to assess the expression of the BIRC5 and BIRC6 genes in normal peripheral blood lymphocytes and in peripheral blood lymphocytes of patients diagnosed with atherosclerosis.Material and methods. The analysis was carried out on RNA samples obtained from peripheral blood lymphocytes of 21 patients with diagnosed atherosclerosis. The specific fragment of the analysed gene was obtained through amplification with the use of cDNA synthesised in the reaction of reverse transcription. The test of expression was conducted with the use of the Real-Time PCR method. In the studied cases, the level of expression of the analysed gene was compared to the level of expression of the reference gene, B2M.Results. The study showed that mRNA of the BIRC5 and BIRC6 genes is present in the cells of patients with atherosclerosis, as well as in the cells of healthy individuals. The cells taken from the patients with atherosclerosis were mainly characterized by an increased gene expression in comparison to the normal cells.Conclusion. Increased BIRC6 and BIRC5 gene expression in the cells of the patients with atherosclerosis can suggest an increased amount of the inhibitor protein BRUCE and survivin, and also decreased sensitivity of cells to apoptosis. In the case of the patients who had significantly higher expression of the BIRC6 gene in lymphocytes compared to the norm, hypertension and diabetes mellitus were more common.